Design mapping categories on Geographic information systems - Robitotul Mu'awanah; Primaadi Airlangga (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Categories are part of the classification system (class, rank type, and so on). In an integrated mapping system, there is a lot of data and types of mapping which will make it difficult to search for data by selecting one by one. To facilitate the search, a search system is created that also supports categorization. The mapping’s category system makes it easier to search for maps according to their respective categories. Therefore, design and construction of mapping category on the geographical information system researching on how to implement categories in the geographical information system, which can then be displayed on the category table, so that the data of category names can be displayed in the form of a table in the category search. In the search category, users can not only fill one category in the search field, but users can fill more than one category. However, the name entered in the search field must match the category name, if it does not match then the category name will not be displayed in the category names table. This method hopefully can help users to find similar or relatable mapping to the one they need.